Brinjal shoot and fruit borer infestation in relation to plant age and season (Bangladesh Journal of Agricultural Research, 2015)
Brinjal shoot and fruit borer infestation varied significantly in relation to plant age and season. The peak shoot infestation was 8.56% in the 10th week of transplanting. No infestation of BSFB was found up to 5 weeks of transplanting. The shoot infestation was initiated in the 6th week of transplanting which increased to a little higher level in the next week. Then it showed an exponential increase of shoot infestation up to 10th week after which it declined steadily. Flowering and fruit setting started in the 9th week of transplanting. Infestation of brinjal shoot and fruit borer (BSFB) shifted to fruits from shoots causing a steady declined in the trend of shoot infestation. Plant age had significant effect (r2=0.87) on fruit infestation. The fruit infestation reached the highest level (38.56%) in 14th week of transplanting. However, the level of infestation at different ages of the plant may vary depending on the location, temperature, variety etc. The shoots and fruits of brinjal plant were found to be infested by BSFB throughout the year, although the level of infestation varied. Maximum shoot and fruit infestation was found in the month of September.Bangladesh J. Agril. Res. 40(3): 399-407, September 2015